EVALUATION OF THE IMPLEMENTATION OF DENGUE HEMORRHAGIC FEVER (P2DBD) PROGRAM IMPLEMENTATION IN PUSKESMAS PAYUNG SEKAKI PEKANBARU (Al Insyirah International Scientific Conference on Health, 2021)
The incidence of dengue fever in Indonesia has increased every year. In particular, in Pekanbaru City, there was an increase in dengue case data in 2019, reaching 274 cases with the highest cases of DHF, namely at Payung Sekaki Health Center with 73 cases. The high number of cases of DHF can be caused by problems in planning and implementing the Dengue Hemorrhagic Fever Control Program (P2DBD) which is not optimal due to the factors that influence it. The optimal implementation of the P2DBD program is basically to reduce the number of DHF cases. This study aims to find out about the Evaluation Results (Input, Process and Output) in the P2DBD Program at Puskesmas Payung Sekaki, Pekanbaru City which was conducted in January-July 2020. This type of research is qualitative research by conducting in-depth structured interviews and observations with 6 research informants. The result of this research is that the input variable for human resources is only 1 person and has a double burden. The process variable shows that there is still a lack of community participation in the implementation of the DHF program, namely the PSN Program, Community Participation and Periodic Larva Examination. The output variable is seen from the larva free rate (ABJ) which decreases and does not match the target. The target for ABJ is 95% while ABJ PKM in 2019 is only 77%. So it can be concluded from the results of the input, process, and output variables that are the constraints, namely HR, there is still a lack of community participation in the implementation of the P2DBD program and the decreasing number of ABJ. It is recommended that the Puskesmas provide recommendations for additional surveillance and epidemiology personnel in the process of implementing the P2DBD program, adding additional jumantik kits, and it is hoped that cadres can be more active in the community to support and participate in the implementation of the P2DBD program.
Keywords: P2DBD Program; Evaluation; Implementation